2021
DOI: 10.1177/20503245211034934
|View full text |Cite
|
Sign up to set email alerts
|

Facing drug addiction: Vietnam’s struggle with opioids

Abstract: Drug addiction is a historical issue in Vietnam. Although Vietnam has a long history as a producer of opium poppies and crossroads for the illicit drug trade, it is now has some of the most stringent drug laws in the world. Vietnam has shown some success in reducing the production, trade, and transportation of narcotics. There has also been a shift in the attitudes of lawmakers and government authorities toward viewing drug abuse as a health problem rather than a social vice. Educating and encouraging citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, Dien Bien and Son La are two mountainous provinces bordering Laos. In these provinces (especially border areas), geographical barriers and rough terrain can facilitate unlawful activities such as growing poppy plans, drug trafficking, and smuggling [ 38 , 39 ]. Patients also can be influenced by their peer drug users and relapse into opioid use since many people are using drugs in these two provinces.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dien Bien and Son La are two mountainous provinces bordering Laos. In these provinces (especially border areas), geographical barriers and rough terrain can facilitate unlawful activities such as growing poppy plans, drug trafficking, and smuggling [ 38 , 39 ]. Patients also can be influenced by their peer drug users and relapse into opioid use since many people are using drugs in these two provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a huge gap in terms of quality education and communication on the principles of harm reduction, stigma, and prevention of drug use ( 24 ). The government tries to justify its fight against drug use with zero tolerance and, second, with massive media campaigns.…”
Section: Proposed Methods To Improve the Perception Of People With Ad...mentioning
confidence: 99%
“…Data from MOLISA (Ministry of Labour, Invalids and Social Affairs) in April 2020 indicated that Vietnam has 97 public drug detoxification facilities, treating 34,982 patients, plus 16 additional approved voluntary drug detoxification facilities countrywide. So far, there are only 13 provinces and cities in Vietnam where family-and community-based detoxification exist (Hieu et al, 2021).…”
Section: Treatment Optionsmentioning
confidence: 99%